The new Avicenna Roboflex: How does the irrigation system work? Results from an in vitro experiment - ŞENER, TARIK EMRE (PAGEPRESS PUBL, 2018)
Introduction: Since 2012 Elmed has been working on a robot specifically designed for flexible ureteroscopy. After the first version of Avicenna Roboflex, a second version was developed in 2015, with significant changes especially in the irrigation system. We consider mandatory for the endourologist that works with the Avicenna Roboflex be aware of the functioning of the irrigation system. Materials and Methods: We connected a container to the pump's irrigation system and measured the quantity of saline per second delivered by each speed setting, with/without the flush in five different modalities: pump on its own, pump with ureteroscope, with two laser fibers, with 1.9 Fr basket, and with a Terumo guidewire. Results: The highest mean flow-rates were observed in the 200-micrometer laser fiber, after the pump on its own. Median flow-rates for all speed settings were significantly higher for the pump on its own than for the URS in both flushed and non-flushed modes (p = 0.045, p = 0.039 respectively). There was no statistically significant difference in median flow-rates between the guide wire and basket in all of the speed settings (p = 0.932 and p = 0.977). For both laser fibers there was no statistically significant difference between the median flow rate on both non-flush and flush modes. (p = 0.590 & p = 0.590). There was a linear correlation between the speed setting and the increase measured with the flush-option for pump only measurements (r = 0.602, p = 0.038). There was no statistically significant difference between laser fibers and the pump on its own on the increase of flow rate with flush mode. (p = 0.443 for the 272-micrometer fiber and p = 0.219 for the 200-micrometer fiber). Conclusion: The irrigation system of the new Avicenna Roboflex is optimized compared to the previous version. However other more complex studies concerning the live flow/pressure relationship are needed before firm conclusions can be made.
Keywords: Renal stone; Ureteroscopy; Avicenna Roboflex; Irrigation system; Flexible ureteroscopy; Intrarenal flow; Urolithiasis; FLEXIBLE URETERORENOSCOPY; FLOW; URETEROSCOPY